Evaluating the Relationship Between Intimate Partner Violence-Related Training and Mental Health Professionals’ Assessment of Relationship Problems - Burns, Samantha C. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is a serious public health problem associated with increased risk of developing mental health conditions. Assessment of IPV in mental health settings is important for appropriate treatment planning and referral; however, lack of training in how to identify and respond to IPV presents a significant barrier to assessment. To address this issue, the World Health Organization (WHO) advanced a series of evidence-based recommendations for IPV-related training programs. This study examines the relationship between mental health professionals? experiences of IPV-related training, including the degree to which their training resembles WHO training recommendations, and their accuracy in correctly identifying relationship problems. Participants were psychologists and psychiatrists (N = 321) from 24 countries who agreed to participate in an online survey in French, Japanese, or Spanish. They responded to questions regarding their IPV-related training (i.e., components and hours of training) and rated the presence or absence of clinically significant relationship problems and maltreatment (RPM) and mental disorders across four case vignettes. Participants who received IPV-related training, and whose training was more recent and more closely resembled WHO training recommendations, were more likely than those without training to accurately identify RPM when it was present. Clinicians regardless of IPV-related training were equally likely to misclassify normative couple issues as clinically significant RPM. Findings suggest that IPV-related training assists clinicians in making more accurate assessments of patients presenting with clinically significant relationship problems, including IPV. These data inform recommendations for IPV-related training programs and suggest that training should be repeated, multicomponent, and include experiential training exercises, and guidelines for distinguishing normative relationship problems from clinically significant RPM.